The tools of cloud technology for learning of fundamentals of mathematical informatics for students of technical universities - Oksana M. Markova (Academy of Cognitive and Natural Sciences, 2018)
Objectives of the study: the development of a common structure of cloud technology tools for learning of fundamentals of mathematical informatics. Research objectives: to classify the resources of cloud study in the basics of mathematical informatics. Object of study: the tools learning the fundamentals of mathematical informatics for students of technical universities. Subject of study: the tools of cloud technology for learning of fundamentals of mathematical informatics. Methods: analysis, synthesis. Research results: the common structure of cloud technology tools for learning of fundamentals of mathematical informatics was developed. Conclusions and recommendations: designed system of cloud technology tools for learning of fundamentals of mathematical informatics can be used in the construction of appropriate methodological system of learning.